The Influence of E-Parliament on the Transparency of Budget Management in the Regional House of Representatives of Ngawi Regency - Regina Zalzabila; Endang Murti; Harianto Harianto (Universitas Tribhuwana Tungga Dewi, 2026)
Effective local governance demands information transparency, particularly in public budget accountability mechanisms. This study aims to examine the effect of implementing an electronic parliament system on the transparency of budget management in the Regional House of Representatives of Ngawi Regency. The conceptual frameworks used in this study include good governance theory, agency theory, and e-government theory. The research method applied is quantitative with an explanatory approach through a questionnaire-based survey distributed to forty-two council members as respondents. Data analysis techniques involve classical assumption tests and simple linear regression analysis. The results show that the electronic parliament has a positive relationship direction with a regression coefficient of 0.504, but this effect is not significant because the t-statistic value is smaller than the t-table and the significance value is greater than the 0.05 threshold. The coefficient of determination indicates a variable contribution of 3%, while the rest is influenced by other factors such as organizational commitment and human resource quality. The main contribution of this study lies in the originality of the empirical testing of legislative digitalization at the second-tier local government level, proving that technology adoption does not automatically guarantee fiscal transparency without organizational readiness.Tata kelola pemerintahan daerah yang efektif menuntut adanya keterbukaan informasi, terutama dalam mekanisme pertanggungjawaban anggaran publik. Penelitian ini bertujuan untuk menguji pengaruh penerapan sistem parlemen elektronik terhadap transparansi pengelolaan anggaran di Dewan Perwakilan Rakyat Daerah Kabupaten Ngawi. Landasan konseptual yang digunakan dalam penelitian ini meliputi teori tata kelola pemerintahan yang baik, teori agensi, dan teori pemerintahan elektronik. Metode penelitian yang diterapkan adalah kuantitatif dengan pendekatan eksplanatori melalui survei menggunakan kuesioner kepada empat puluh dua anggota dewan selaku responden. Teknik analisis data menggunakan uji asumsi klasik dan analisis regresi linier sederhana. Hasil penelitian menunjukkan bahwa parlemen elektronik memiliki arah hubungan positif dengan koefisien regresi sebesar 0,504, namun pengaruh tersebut tidak signifikan karena nilai t-hitung lebih kecil dari t-tabel serta signifikansi lebih besar dari taraf 0,05. Koefisien determinasi menunjukkan kontribusi variabel sebesar 3%, sedangkan sisanya dipengaruhi faktor lain seperti komitmen organisasi dan kualitas sumber daya manusia. Kontribusi utama penelitian ini terletak pada orisinalitas pengujian empiris digitalisasi legislatif di tingkat pemerintah daerah tingkat dua, yang membuktikan bahwa adopsi teknologi tidak serta-merta menjamin keterbukaan fiskal tanpa kesiapan aspek organisasional.